Validity of session rating of perceived exertion assessed via the CR100 scale to track internal load in elite youth football players - Naidu, S. A.; Fanchini, M.; Cox, A.; Smeaton, J.; Hopkins, W. G.; Serpiello, F. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess the convergent validity of the Borg CR100® scale to track internal training load (TL) in youth football players. Methods: A total of 19 youth football players (age = 15 [1] y, height = 175.9 [12.3] cm, and body mass = 69 [15.4] kg) were monitored for 27 sessions, including training and games. Internal TL was assessed via session rating of perceived exertion (sRPE) and 2 heart-rate-based methods (Banister training impulse and Edwards TL). The correlations between sRPE and heart-rate-based TL, the differences in individual player intercepts and slopes, and the differences between types of sessions (training vs games) were assessed using a general linear mixed model with magnitude-based inferences. Results: Correlations between sRPE and Banister training impulse were very large at overall group level (r = .77; 90% confidence limits, .72-.80) and individual level (range .70-.95). Correlations between sRPE and Edwards TL were very large at overall group level (r = .84; 90% confidence limit, .82-.86) and large to very large at individual level (range .64-.93). A very likely small difference was found in the comparison between games and training sessions for the relationship between sRPE and Banister training impulse. Conclusions: The Borg CR100 scale is a valid method for monitoring TL in youth football players..